Constitutive modeling of size effect on deformation behaviors of amorphous polymers in micro-scaled deformation. (February 2017) - Deng, Y.J.; Peng, L.F.; Lai, X.M.; Fu, M.W.; Lin, Z.Q.
Abstract: With the advantages of high-formability, low-cost and unique physical properties, polymers have been widely used in microforming of polymeric components for a large scale of applications in many fields including micro-optics, microfluidic and sensors, etc. In micro-scale, the deformation behaviors of polymers are observed to be size-dependent. Conventional constitutive models of polymers, however, cannot predict and represent those size-dependent behaviors well. To address this issue, a constitutive model with consideration of size effect for amorphous polymers in micro-scale was developed in this research. Firstly, on the basis of the couple stress theory, the impact of rotational gradients was taken into consideration and a strain gradient "elastic-viscoplastic" constitutive model was proposed to quantitatively describe the size-dependent behaviors of amorphous polymers in micro-scale. After that, four point micro-bending experiments were implemented on poly (methyl methacrylate) (PMMA) films with thickness varying from the millimeter scale to micrometer scale. The size effect of PMMA in micro-scale was further illustrated and the proposed strain gradient "elastic-viscoplastic" model was finally validated and verified for the capability of modeling of the size effect of amorphous polymers in micro-scaled deformation. This research thus advances the understanding of the size effect and the strain gradient based mechanical behaviors of amorphous polymers and facilitates its applications in industries. Highlights: A strain gradient elastic-viscoplastic model of amorphous polymers is proposed. Size effects on both elasticity and plasticity of amorphous polymers are observed. The elastic and plastic intrinsic lengths are 0.062 and 0.034 mm for PMMA.